Phosphorus biofortification of Pleurotus floridanus Singer and its effecton fruit body yield and phosphorus bioavailability: Biofortification of Pleurotus floridanus using Phosphorus Supplement - Adedokun, Olutayo Modupeola; Robert, Vivian; Nnyam, Lebatam; Odiketa, Jeremiah Kelechi; Whitehall, Stuart (Mushroom Research, 2024)
Phosphorus is an essential mineral needed for the growth, maintenance, and repair of all tissues and cells. This study was designed to biofortify Pleurotus floridanus with phosphorus supplements and assessed its effect on the yield and phosphorus contents. Phosphorus supplement was added to mushroom growth media. The experiment was set in Completely Randomized Design with five replicates. The result showed a positive effect of phosphorus supplementation on the number of mushroom fruit bodies, duration to fruiting and harvesting, and wet & dry weight of fruit bodies. Proximate analysis of treated samples had lower carbohydrate, higher fibre, lower lipid compared with the normal control. Phosphorus content was higher in control compared with treated samples. Conclusively, P is an essential element and it may be important to use the appropriate type of phosphate sources to ensure itsavailability.